Highly significant correlation between rates of adverse childhood experiences (ACE) in youth survivors of child sexual abuse (CSA) and their biological mothers - Matthew Reeson; Hannah Pazderka; Wanda Polzin; Vincent Agyapong; Andrew J. Greenshaw; Yifeng Wei; Laurie Syzmanski; Peter H. Silverstone (PLoS ONE, 2026)
Background Adverse Childhood Experiences (ACE) have been associated with poor long-term mental health outcomes. Measuring ACE scores in youth undergoing treatment, as well as their caregiver(s), may help inform treatment approaches and practice. This novel study examined a unique sample to attempt to help elucidate the relationship of trauma histories between youth survivors of child sexual abuse (CSA) and their biological mothers. Secondarily, we aimed to examine the distribution of ACE scores in order to evaluate if they demonstrate common underlying factors. Materials and methods Children and adolescent CSA survivors aged 8–17 who were enrolled into a comprehensive multimodal 1-year treatment program for their abuse completed the Center for Youth Wellness ACE Questionnaire (CYW ACE-Q). Secondarily, a caregiver of each child was asked to complete the original 10-item ACE questionnaire (ACE-Q). Based on the available data, we report findings from a convenience sample of biological mothers of the CSA survivors. Biological mother ACE scores were statistically compared to determine if their trauma histories were associated with their child’s ACE score. Secondarily, a Principle Factor Analysis (PFA) was conducted to assess any underlying common factors among reported ACE scores. Results A statistically significant moderate positive correlation was found between the biological mother and their child CSA survivor in terms of their ACE scores (r(107) = 0.56, p < 0.0001). Examining the underlying factor structure of the ACE scores, two factors (which we labelled neglect and abuse ) accounted for the most variance in our sample (41.7%). Conclusions The results of this study demonstrate a surprisingly strong, and highly statistically significant, correlation in the rates of high ACE scores between child CSA survivors and their biological mothers. These results strongly support the need for trauma-informed approaches when working with CSA survivors, and in particular all treatment approaches should also consider parental trauma histories. The findings of this study suggest that a family-centered, trauma-informed care approach should be considered, instead of only programming which is focused on the impacted child.